Unusual Presentation of Precocious Puberty Associated with Primary Hypothyroidism in a 8.5 Years Old Girl (Delta Medical College Journal, 2018)
Precocious puberty is one of the gynaecological problems in childhood. Children with hypothyroidism generally have delayed pubertal development. But primary hypothyroidism is one of the rare causes of precocious puberty especially in long standing untreated patients. Bilateral ovarian enlargement due to multiple cystic ovaries is a rare complication of primary hypothyroidism. For ovarian enlargement no treatment is required at all. This is a case report of an 8.5 years old girl diagnosed as a case of precocious puberty with benign ovarian tumour at a peripheral hospital and was being prepared to undergo laparotomy. When patient was admitted at Shaheed Suhrawardy Medical College Hospital (ShSMCH), Dhaka, Bangladesh, after thorough investigations primary hypothyroidism was diagnosed. She was given thyroxin replacement and close monitoring was done by doing USG of uterus and adnexae, thyroid function test at monthly interval. USG after 2 months revealed significant reduction of ovarian volume and at 6 month ovarian volume reduced to normal. It was also noticed that the rate of reduction of ovarian volume corresponds to the rate of reduction of serum TSH level measured serially at every 2 months interval.Delta Med Col J. Jan 2018 6(2): 102-105